1989
DOI: 10.1530/jrf.0.0870763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social stress during early pregnancy on litter size and sex ratio in the golden hamster (Mesocricetus auratus)

Abstract: Primiparous female hamsters were mated to proven breeders and stressed during early pregnancy. Females were housed singly throughout gestation except for Days 4, 5 and 6 when they were paired for 10-min intervals 3 times each day with another female matched for age, weight and day of pregnancy. Within each of the pairs, one female was consistently dominant to the other. Controls were exposed to a novel area instead of a conspecific. At parturition, all pups were counted, sexed and weighed. There were no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0
6

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 38 publications
4
45
0
6
Order By: Relevance
“…Some results suggest that maternal stress can negatively impact on the embryo even at very early stages of its development. For instance, it has been shown that litter sizes of female hamsters stressed during early pregnancy were significantly smaller than those of controls, with fetal loss occurring between days 5 and 10 of pregnancy (Pratt & Lisk 1989). In humans, it has been demonstrated that pregnancies characterized by increased maternal cortizol (commonly used stress marker) during the first three weeks after conception are more likely to result in spontaneous abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Some results suggest that maternal stress can negatively impact on the embryo even at very early stages of its development. For instance, it has been shown that litter sizes of female hamsters stressed during early pregnancy were significantly smaller than those of controls, with fetal loss occurring between days 5 and 10 of pregnancy (Pratt & Lisk 1989). In humans, it has been demonstrated that pregnancies characterized by increased maternal cortizol (commonly used stress marker) during the first three weeks after conception are more likely to result in spontaneous abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Методика вiдтворення вказаного типу стре-су пiд час гестацiї та отримання нащадкiв описано в роботi N. C. Pratt, R. D. Lisk [15]. Умови утримання всiх нащадкiв вiд наро-дження до 11-мiсячного вiку були iдентични-ми та вiдповiдали рекомендацiям по утри-манню щурiв [16].…”
Section: матерIали та методиunclassified
“…Dev. 55: [529][530][531][532][533]2009) he sex ratio of mammals (humans, rodents and ruminant ungulates) has been shown to be affected by many factors, such as nutrition, season, disease, levels of gonadotrophin and steroid hormones, social status, stress, age and parity [1][2][3][4][5]. In the 1970s, Trivers and Willard [6] hypothesized that the physical condition of the individual female during the periods of maternal investment influences the sex ratio of progeny.…”
mentioning
confidence: 99%
“…Stresses can be acute (short term), such as earthquakes, floods or sudden bereavement, or chronic (long term), such as food shortages, wars or epidemics. In rodents, females stressed acutely in some manner tend to produce fewer sons than non-stressed females [2,3,7]. The concentration of cortisol or corticosterone in plasma is used to assess stress [8].…”
mentioning
confidence: 99%